Profil Sumber Daya Manusia pada Lembaga Eksekutif Nagari di Sumatera Barat - Effendi, Syafnil (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2003)
This article aimed at describing the profileÂ of â€œNagariâ€ Government officers all the province of West Sumatera including their formal and informal educations, experiences, achievement motivations, and mental health (personalities) in carrying out their main duties. For this purpose qualitative approach was used through â€œmean and percentageâ€ analysis.Â The finding of this research indicated that in general their formal and formal educations tend to be in sufficient enough to support their duties, while their experiences tend to be less sufficient. Besides, their achievement motivations and mental health (personalities) tend to be in low grades or categories Kata Kunci: Profil Sumber Daya Manusia, Lembaga Eksekutif Nagari